Clinical and Microbiological Evaluation of Brazilian Red Propolis Containing-Dentifrice in Orthodontic Patients: A Randomized Clinical Trial. (22nd January 2020) - Furtado Júnior, João Hildo de Carvalho; Valadas, Lídia Audrey Rocha; Fonseca, Said Gonçalves da Cruz; Lobo, Patrícia Leal Dantas; Calixto, Lays Helena Maia; Lima, Ana Gleyce Ferreira; de Aguiar, Maria Helena Ramos; Arruda, Isadora Sousa; Lotif, Mara Assef Leitão; Rodrigues Neto, Edilson Martins; Fonteles, Marta Maria de França
Abstract : Aim . To evaluate the efficacy of dentifrice containing brazilian red propolis (BRP) in adolescents under orthodontic treatment. Materials and Methods . This is a randomized, double-blind, clinical trial. A total of 92 participants free from caries were randomized into 2 groups; the first received fluoride dentifrice, and the second received fluoride dentifrice incorporated with BRP. The gingival bleeding index (GBI) was recorded, and saliva was collected on the baseline (D0) and after 28 days (D28) for microbiological analysis. Data from GBI and Colony Forming Units (CFU) (log10 ) were expressed as mean and standard deviation. Results . The two groups reduced GBI significantly, with no difference in the intergroup analysis. In the intragroup analysis, it was observed that G2 (p < 0.001 ) had a significant reduction for Gram-negative bacteria, while there was significance (p < 0.001 ) in the intergroup analysis when compared with G1. For S. mutans bacteria, it was observed that only G2 had a statistically significant reduction (p < 0.001 ), and there was significant reduction (p = 0.006 ) in the intergroup analysis of the G2 group when compared with G1. Conclusions . Dentifrice containing BRP demonstrated better clinical and microbiological activity. Future studies are needed to better identify effects to establish the use of dentifrice containing propolis in biofilm control.